Theme and Counter-Theme in Contemporary Spirituality - Cenkner, William (Horizons, 1982)
The contemporary religious seeker often experiences the feeling of being about to be quartered by wild horses running in opposite directions. Such a person recognizes the situation that Yeats describes in "The Second Coming":Things fall apart; the centre cannot hold;Mere anarchy is loosed upon the world,The blood-dimmed tide is loosed, and everywhereThe ceremony of innocence is drowned;The best lack all conviction, while the worstAre full of passionate intensity.